STRATEGI PEMBELAJARAN BAHASA ARAB AL-ASHWAT DI DALAM MENINGKATKAN KETERAMPILAN MENYIMAK MAHASISWA JURUSAN PENDIDIKAN BAHASA ARAB UNIVERSITAS ISLAM NEGERI MATARAM - HIDAYATULLOH, IRZA; Suparmanto, Suparmanto; Nasikin, Moh (Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
Al-Ashwat (الأصوات) comes from arabic, which is the plural form of the word shaout (صوت) which means sound or sound. Al-Ashwat became a term for the study of Arabic language science, which is an Arabic discipline that recites sound or sound systems. This science examines the sounds and various sounds that are produced by human speech tools. In the teaching of al-ashwat there are at least two learning methods that pay attention to the teaching of language sounds the two methods are the Phonetic Method and the Mim-mem Method. The al-ashwat method that can improve listening skills (maharatul istima') is the Phonetic Method. The application of the al-ashwat method, namely the Phonetic Method, to learn listening skills (maharatul istima') Istima' 1 Course, Department of Arabic Language Education, Mataram State Islamic University. This research uses qualitative methods, data collection techniques using observation, interviews and documentation. The data analysis technique uses data reduction and data verification techniques. The results of this study provide information that istima'1 learning using the phonetic method in the Arabic Language Education Department of Mataram State Islamic University has been well arranged. However, in its application there are still obstacles, both internal and external constraints. The application of this method in order to obtain maximum results as expected, namely students are able to understand the sounds or sounds they hear, are able to recite what they hear, and can pour the results they hear into a piece of writing. So that this method is appropriate to be used in learning Istima' Skills in the Department of Arabic Language Education, Mataram State Islamic University.